ANALISIS KOMPONEN KETERAMPILAN MENGELOLA KELAS DAN PEMBERIAN PENGUATAN KARAKTER PESERTA DIDIK DALAM PENGAJARAN MIKRO PADA MAHASISWA PENDIDIKAN FISIKA - Dyah Pratiwi, Sri Septi; Budi Prastowo, Sri Handono; Sudarti (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2022)
The purpose of this research is to analyze the components of classroom management skills and provide reinforcement by teachers to learners. The research method used is the descriptive method. The type of research used is correlational using quantitative and qualitative approaches. Data collection techniques use literacy and observation studies when learning practices through direct video recording observation. The respondents used 13 practices in microteaching teaching courses at the Faculty of Teacher Training and Education, University of Jember. The results showed that practical skills in managing classes were still not good. This is evidenced by the percentage number of calculation results of each skill component. The behavioral component obtained a score of 71.2%, the skill component divided attention 79.3%, the skill component focused the group's attention 64%, the skill component demanded the responsibility of learners 55% and the skill component gave clear instruction 50%. The results of research on practical strengthening skills are already included in the good category. Proven in the value of the skill component which shows more than 50%. In the verbal reinforcement, component obtained a value of 82%, the component of non-verbal strengthening skills 65.5%, the skill component of how to strengthen 78.25%, and the skill component of the principles of strengthening 73.25%. Respondents who mastered both skills were the 11th student.